THE USE OF WRITTEN FEEDBACK TECHNIQUE TO IMPROVE THE PRACTICE OF GRAMMAR FOR SENTENCE WRITING COMPETENCE - Wijayanti, Puspa; Linggar Bharati, Dwi Anggani; Mujiyanto, Januarius (English Education Journal, 2015)
This thesis was purposed to (1) find out the problems that faced by grade 3 students of Mondial School in mastering grammar (2) explain the implementation of written feedback in practicing grade 3 studentsâ grammatical correct writing (3) explain the extent to which the practice of the written feedback improves the grade 3 studentsâ grammatical correct writing. I used two cycles. Cycle 1 consisted of some activities, such as pre-observation study, planning, giving out the pre- questionnaire and pre-cycle 1 test, observation and correction through written feedback and making analysis and reflection of the studentsâ pre cycle 1 test. Cycle 2 had the same activities like cycle 2. I got the data from interview, pre questionnaire, and observation in the class, pre cycle 1 test result, post questionnaire and post cycle 1 test results. Then, all the data were analyzed in qualitative and supported by quantitative research. The cycle 1 showed that the students do need more extra grammar practice. Because of the result, I re- planned and changed little the method of the practice in cycle 2. It worked and showed that the written feedback that improved studentsâ writing skill in correct grammar through the regular practices.